Duck!: Scaling the height of a horizontal barrier to body height - Stefanucci, Jeanine K. (2010)
Recent research shows that the body is used to scale environmental extents. We question whether the body is used to scale heights as measured by real actions (Experiments 1 and 2), or judgments about action and extent made from a single viewpoint (Experiments 3 and 4). First, participants walked under barriers either naturally or when wearing shoes or a helmet. Participants required a larger margin of safety (ducked at shorter heights) when they were made taller. In follow-up experiments, participants visually matched barrier heights and judged whether they could walk under them when wearing shoes or a helmet. Only the helmet decreased visually matched estimates; action judgments were no different when taller. The final experiment suggested that the change in matched estimates may have been due to lack of experience wearing the helmet. Overall, the results suggest that perceived height is scaled to the body and that when body height is altered, experience may moderate the rescaling of height.